Comparative analysis of the profit efficiency levels among the major actors in broiler value chain in Ghana - Bombason Kweku Tuoho; Samuel Kwesi Ndzebah Dadzie; Julius Kofi Hagan; Martin Bosompem; Edward Adu-Kyei (Cogent Food & Agriculture)
The Broiler value chain (BVC) is made up of activities that offer business opportunity to the private sector, stimulate economic growth, and provide animal protein for the populace. This study assessed the profitability of major economic activities along the BVC. The quantitative research method was used to collect cross-sectional data. The simple random sampling technique was used to select 345 broiler producers in the Greater Accra, Ashanti, and Bono Regions. A census was employed to take data from 40 poultry processors, and 123 live bird sellers (marketers). Data collection was done with structured interview schedules, and analysed with translog profit function, Gross margin and ANOVA using R and IBM SPSS statistical packages. Broiler producers had a gross margin (GM) of GH¢ 28.4 per bird and a profit efficiency level of 62.9%; a live bird seller’s GM per bird was GH¢ 28.2 and a profit efficiency level of 34.4%; and a poultry processor had a GM per bird of GH¢ 20.9 and a profit efficiency level of 79.9%. The results of ANOVA analysis also showed a statistically significant difference in the GM per bird received and profit efficiency levels obtained by the BVC actors. It is recommended that live bird sellers and broiler producers endeavour to reduce inefficiencies in their marketing and production activities. Government and other development partners should make available the appropriate technologies and training to build the capacity of BVC actors to adequately combine productive resources available to them in order to reduce profit inefficiency and increase production.